Happiness, social fantasy, and the Indonesian novel - Aprinus Salam; Novi Anoegrajekti; Marisa Santi Dewi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
Disinclined to discuss â€œhappinessâ€ in its fundamental context. This study investigates why happiness proves challenging to incorporate as a primary subject in literary works. The prominent focus and originality of this study is the role of happiness concerning the social position, characters, and setting within the narrative structure. Six works: Sitti Nurbaya, Salah Asuhan, Belenggu, Ronggeng Dukuh Paruk, Wasripin dan Satinah, and Bumi Manusia represent storytelling that infrequently portrays happiness. Within these works, a qualitative approach is used in selecting data based on purposive sampling. On the one hand, the analysis requires a conceptual framework on happiness that is grounded in eudaimonia and its subsequent derivative concepts. Eudaimonia translates as â€œflourishingâ€ or â€œwell-beingâ€ and is often equated with living wisely. On the other hand, Å½iÅ¾ekâ€™s theory of social fantasy also assists this research by exploring how narratives shape our understanding of the social environment. A fantasy that â€œteaches us how to desireâ€. The analysis shows that the characters in those novels have the potential to achieve happiness. Nevertheless, the social fantasy of society (the authors) encounters limitations in identifying a model of happiness, prompting an exploration of religious and/or spiritual dimensions. The situations of happiness are more of a pursuit than a reason. Ultimately, this study contributes to contemporary literary criticism related to happiness and social context. The social structuration lies at the state level, where the dominance of ideological frameworks overlooks the fulfilments of (social) justice, humanity, unity, and even divinity.